A Functional Polymorphism-Mediated Disruption of EGR1/ADAM10 Pathway Confers the Risk of Sepsis Progression - Feng Chen (American Society for Microbiology, 2019)
ABSTRACT Increasing evidence has indicated that single nucleotide polymorphisms (SNPs) are related to the susceptibility of sepsis and might provide potential evidence for the mechanisms of sepsis. Our recent preliminary study showed that the ADAM10 genetic polymorphism was clinically associated with the development of sepsis, and little is known about the underlying mechanism. The aim of this study was to confirm the association between the ADAM10 promoter rs653765 G→A polymorphism and the progression of sepsis and to discover the underlying mechanism. Clinical data showed that the rs653765 G→A polymorphism was positively correlated with the development of sepsis, as evidenced by a multiple-center case-control association study with a large sample size, and showed that EGR1 and ADAM10 levels were associated well with the different subtypes of sepsis patients. In vitro results demonstrated that the rs653765 G→A variants could functionally modulate ADAM10 promoter activity by altering the binding of the EGR1 transcription factor (TF) to the ADAM10 promoter, affecting the transcription and translation of the ADAM10 gene. Electrophoretic mobility shift assay (EMSA) followed by chromatin immunoprecipitation (ChIP) assay indicated the direct interaction. Functional studies further identified that the EGR1/ADAM10 pathway is important for the inflammatory response. EGR1 intervention in vivo decreased host proinflammatory cytokine secretion and rescued the survival and tissue injury of the mouse endotoxemia model. IMPORTANCE Sepsis is characterized as life-threatening organ dysfunction, with unacceptably high mortality. Evidence has indicated that functional SNPs within inflammatory genes are associated with susceptibility, progression, and prognosis of sepsis. These mechanisms on which these susceptible sites depended often suggest the key pathogenesis and potential targets in sepsis. In the present study, we confirmed that a functional variant acts as an important genetic factor that confers the progression of sepsis in a large sample size and in multiple centers and revealed that the variants modulate the EGR1/ADAM10 pathway and influence the severity of sepsis. We believe that we provide an important insight into this new pathway involving the regulation of inflammatory process of sepsis based on the clinical genetic evidence, which will enhance the understanding of nosogenesis of sepsis and provide the potential target for inflammation-related diseases.